Rémond de Saint-Mard - Myers, R (Voltaire Foundation, 2017)
Introduction Chapter I. The Dialogues de Dieux Chapter II. The Lettres Galantes et Philosophiques Chapter III. Rémond's Aesthetics Chapter IV. Le bon goût Chapter V. The Réflexions sur la poësie en général Chapter VI. Rémond and his critics Lucilie ou l'histoire de mademoiselle de *** List of the works of Rémond de Saint-Mard